PENINGKATAN KAPASITAS WIRAUSAHA DAN KELEMBAGAAN PADA PETANI MILENIAL DI KABUPATEN KEBUMEN - Siti Barokah; Viki Adi Nugroho; Jaelani Gunawan; Ludiantoro (Aspirasi Masyarakat, 2024)
This community service activity aims to enhance the entrepreneurial capacity of millennial farmers through training and the application of modern agricultural technology. Recognizing the importance of the agricultural sector for economic growth and poverty reduction, this activity is designed to address the challenges faced by young farmers, such as limited access to capital, technology, and markets. Through an integrated training method that includes entrepreneurship education, the use of smart agricultural tools, and digital marketing strategies, participants can acquire the knowledge and skills necessary to sustainably manage agricultural enterprises. The results of this activity show a significant increase in participants' understanding of entrepreneurial practices, as well as their ability to formulate innovative business plans. Additionally, networking between farmers and other stakeholders has been strengthened, improving their access to resources and markets. These findings indicate that a holistic approach to capacity building in entrepreneurship can have a significant positive impact on millennial farmers, thereby supporting sustainable rural economic development.